Application of the Problem Based Instruction (PBI) Learning Model to Improve Student Learning Outcomes at SMA N 1 Nggoa - Arni Kopilau Ratu; Vidriana Oktoviana Bano; Yohana Ndjoeroemana (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this research is to improve student learning outcomes in using the problem based instruction learning model in biology subjects. This research is a classroom action research (CAR) which was carried out in the pre-cycle, cycle 1 and cycle II activities with 26 students. Increasing the cognitive domain of students who completed the pre-cycle stage reached 34%, cycle I with an average of 72.11 and the number of students who completed 70% and did not complete 30%, and cycle II with an average of 78.26 students who completed reached 89% and incomplete 11.53%, while in the affective domain stage of cycle I the predicate was very good 3 people who achieved the predicate were good 13 people, the predicate was enough 5 people and the predicate was lacking 5 people and experienced an increase in cycle II reaching 14 predicate very good, predicate good 11 people , the predicate is enough for 1 person and the predicate is lacking. It can be concluded that the application of the problem based instruction model can improve student learning outcomes in class X MIPA 2 on mushrooms at SMA N 1 Nggoa